PENGARUH KEMAMPUAN SOFTSKILL KARYAWAN TERHADAP KEPUASAN MAHASISWA DIBIDANG PELAYANAN DITINJAU DARI SISI GENDER PADA FAKULTAS EKONOMI UNIVERSITAS DHARMA ANDALAS PADANG - Yusnaena Syahrul Effendy dan Syahril (Menara Ilmu, 2016)
This research will discuss about the Effects of Employee Softskill Ability initiative, Commitment, Creativity, Communication, Integration and Discipline Against Student Satisfaction in ministry in terms of the gender At the Faculty of Economics, University of Andalas Padang Dharma, data from this study by using a cross sectional survey. The analytical tool used is multiple linear regression models. The study population was all the students of the Department of Management FEB Unidha Padang were female. active in the academic year 2015/2016 running and samples were taken as many as 100 people using Random Sampling technique Acidental with research initiatives variable, variable communication, integrity, discipline variable positive and significant impact to the satisfaction of temporary variables and variable commitment Creativity, no effect significantly to the Student Satisfaction UNIDHAKeywords: Ability soft skills, gender, student satisfaction